KARAKTERISTIK DESAIN KURIKULUM HOMESCHOOLING TUNGGAL “SOLO HOMESCHOOLING” STUDI KASUS: SOLO HOMESCHOOLING SURAKARTA - Siti Shofiyatun; Septi Aprilia (Lembaga Pengembangan Kinerja Dosen, 2022)
In Solo, there are 4 families that have organized homeschooling, one of is Mr. Hidayat's family . Their children previously could not enjoy their study, after switching to homeschooling their children are happier when learning, critical, creative and have high curiosity. How is the curriculum design applied in single homeschooling